Britain, the US and China's anti-Soviet stance in the Cold War : containment and trade, 1977-1980 - Pierri, Bruno, 1971- 1971- (Cold War history, 2024)
This book shows how international trade was a key part of the classic Western policy of containment towards the Soviet Union in the Cold War in the late 1970s